2014
DOI: 10.1002/hep.27094
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of hepatocyte senescence after continuousin vivocell proliferation

Abstract: A better understanding of hepatocyte senescence could be used to treat age-dependent disease processes of the liver. Whether continuously proliferating hepatocytes could avoid or reverse senescence has not yet been fully elucidated. We confirmed that the livers of aged mice accumulated senescent and polyploid hepatocytes, which is associated with accumulation of DNA damage and activation of p53-p21 and p16 ink4a -pRB pathways. Induction of multiple rounds continuous cell division is hard to apply in any animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 39 publications
5
83
0
Order By: Relevance
“…57 Another study of liver proliferation in aged mice revealed that p16 is elevated in livers of old mice and contributes to the weak proliferative response of livers to PH. 58 Studies of 130 old human patients who underwent hepatectomy showed that these patients had much higher levels of p16 and that these levels negatively correlated with liver regeneration. 59 Examination of mutation/expression of p16 and Rb proteins in human liver cancer and in animal models of carcinogenesis strongly indicated that the loss of functions of these proteins is involved in development of severe liver cancer.…”
Section: 54mentioning
confidence: 99%
“…57 Another study of liver proliferation in aged mice revealed that p16 is elevated in livers of old mice and contributes to the weak proliferative response of livers to PH. 58 Studies of 130 old human patients who underwent hepatectomy showed that these patients had much higher levels of p16 and that these levels negatively correlated with liver regeneration. 59 Examination of mutation/expression of p16 and Rb proteins in human liver cancer and in animal models of carcinogenesis strongly indicated that the loss of functions of these proteins is involved in development of severe liver cancer.…”
Section: 54mentioning
confidence: 99%
“…As a result, hepatocytes that reside at the upstream periportal zone differ from hepatocytes in the downstream perivenous zone in the expression of key metabolic genes, a phenomenon termed 'metabolic zonation' (Gebhardt 1992;Jungermann and Keitzmann 1996;Braeuning et al 2006;Colnot and Perret 2011). A second ubiquitous source of liver heterogeneity is its polyploidy (Celton-Morizur et al 2009;Celton-Morizur and Desdouets 2010;Duncan et al 2010;Pandit et al 2012;Gentric and Desdouets 2014;Wang et al 2014;Duncan 2013). Unlike most tissues, the liver is a mixture of hepatocytes that contain either one or two nuclei, each with either 2, 4, 8 or more haploid chromosome sets.…”
Section: Introductionmentioning
confidence: 99%
“…However, the discovery of ploidy conveyor 63 has opened a new vision of the field. Polypoidy reversibility explains how polyploid hepatocytes could produce diploid progeny in order to match the low level of youthful liver and restore the proliferative capacity 122 . For instance, after xenotransplantation, old hepatocytes could repopulate the liver to the same degree that 2-month-old hepatocytes did.…”
Section: Binucleation and Chemical-driven Liver Damagementioning
confidence: 99%
“…Rise in the binucleation rate is more frequent than other polyploid forms 114 Ploidy conveyor would also allow hepatocytes respond to xenobiotic or nutritional injury 63 Adaptative response to loss of function by acquiring more gene copies 122 Oxidative stress may play a main role in binucleation induction 115 Final result of compensatory liver growth after injury 117 kinase 3 beta (GSK3b) have been described as cytoskeleton regulators [68][69][70] . Similarly, excess glucose feeding to intact mice resulted in polyploidization of pancreatic b cells 71 .…”
Section: Chemical-induced Liver Injurymentioning
confidence: 99%